Características do poder político em Hobbes - Costa, Paula Giovanna (2020)
The present work has as its central objective the investigation of the construction of Hobbesian political power and, specifically, the origin of such power. It also analyzes the dichotomy between Aristotle's and Hobbes's stances. The guiding thread focuses on explaining ancient and modern thoughts on the subject. The first is based on the Aristotelian conception and the second on Hobbes' materialist nature. The subject is problematized when compared to other modern philosophical writings. Thus, the exam covers the philosophy of antiquity to the present and concludes with open questions in the scenario of recent political philosophy.